2012
DOI: 10.1073/pnas.1118687109
|View full text |Cite
|
Sign up to set email alerts
|

Honesty mediates the relationship between serotonin and reaction to unfairness

Abstract: How does one deal with unfair behaviors? This subject has long been investigated by various disciplines including philosophy, psychology, economics, and biology. However, our reactions to unfairness differ from one individual to another. Experimental economics studies using the ultimatum game (UG), in which players must decide whether to accept or reject fair or unfair offers, have also shown that there are substantial individual differences in reaction to unfairness. However, little is known about psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…The work by Takahashi et al (1) recently reported a negative association between brainstem serotonin transporters and personality traits such as honesty and rejection to unfairness. They interpret their locus within brainstem to include the dorsal raphe nucleus (DRN) (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Takahashi et al (1) recently reported a negative association between brainstem serotonin transporters and personality traits such as honesty and rejection to unfairness. They interpret their locus within brainstem to include the dorsal raphe nucleus (DRN) (1).…”
mentioning
confidence: 99%
“…They interpret their locus within brainstem to include the dorsal raphe nucleus (DRN) (1). Other than DRN, the median raphe nucleus (MRN) also projects to the forebrain and may be equally important in the serotonergic modulation of cortical activity.…”
mentioning
confidence: 99%
“…
Yang et al (1) argue that sex and age are confounding factors in our study (2). However, by definition, they actually are not.
…”
mentioning
confidence: 72%
“…In a recent article, Takahashi et al (1) described interesting work regarding the mediating effect of honesty in the relationship between serotonin and reaction to unfairness. After reading the article with interest, we have some concerns about the study.…”
mentioning
confidence: 99%
“…First, only male subjects were investigated in their study (1). Sex differences in the serotonin system and personalities would potentially confound the results.…”
mentioning
confidence: 99%